2022
DOI: 10.3389/fgwh.2022.801092
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Preterm Birth Among Pregnant Women Admitted at the Labor Ward of the Komfo Anokye Teaching Hospital, Ghana

Abstract: Preterm birth is a global epidemic and a leading cause of neonatal mortality in Sub-Saharan Africa. We evaluated the prevalence and risk factors of preterm birth among women attending the labor ward for delivery at a tertiary hospital in Ghana. This comparative cross-sectional study was conducted among a cohort of 209 pregnant women admitted to the labor ward of the Komfo Anokye Teaching Hospital (KATH). Pregnant women who delivered between 28 and 36 completed weeks of gestation were classified as preterm deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
3
8
1
Order By: Relevance
“…Teenage mothers (thus, mothers aged less than 20 years) were 13 times more likely to deliver prematurely. An analogous pattern was found among Brazilian (16) and Nigerian (11) mothers who were less than 20 years old with an increased risk of preterm births but incongruent with some retrospective studies in Southern Ghana (7,17) , Kenya (10) , and Ethiopia (12) . Teenagers (young mothers) are still in the active phase of physiological, psychological, emotional, biological, and physical maturity and development.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Teenage mothers (thus, mothers aged less than 20 years) were 13 times more likely to deliver prematurely. An analogous pattern was found among Brazilian (16) and Nigerian (11) mothers who were less than 20 years old with an increased risk of preterm births but incongruent with some retrospective studies in Southern Ghana (7,17) , Kenya (10) , and Ethiopia (12) . Teenagers (young mothers) are still in the active phase of physiological, psychological, emotional, biological, and physical maturity and development.…”
Section: Discussionsupporting
confidence: 64%
“…By applying margin of error (e) of 5%, and standard normal variate (z) at 95% confidence level of 1.96, the sample size was initially estimated at 339. The final sample size was rounded off to 356 after adding 5.0% non-response rate (7) . Afterward, probability proportional to size technique was used to estimate the sample sizes for the five major public health facilities in the study area (Table 1).…”
Section: Sample Size and Sampling Methodsmentioning
confidence: 99%
“…4 Previous studies showed that preterm birth and stillbirths are associated with maternal problems, such as hypertensive disorders of pregnancy, nonobstetric complications, obstetric hemorrhage, and pregnancy-related infections. 5,6 Reduction in maternal mortality can be achieved by making health services available, accessible, and of quality to women in cases of complications related to pregnancy and childbirth. [7][8][9] The most common evidence-based practice for improving quality care includes active referral and actionable information systems, adequate flow of communication, respect, dignity preservation, supporting women emotionally, engagement of talented and motivated human resources, and making available essential physical infrastructure or resources.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that preterm birth and stillbirths are associated with maternal problems, such as hypertensive disorders of pregnancy, nonobstetric complications, obstetric hemorrhage, and pregnancy‐related infections 5,6 . Reduction in maternal mortality can be achieved by making health services available, accessible, and of quality to women in cases of complications related to pregnancy and childbirth 7–9 .…”
Section: Introductionmentioning
confidence: 99%
“…membrane rupture, caesarean section, polyhydramnios and fetal macrosomia [3][4][5][6]. GDM prevalence is estimated to be about 15% globally [7] and varies between 2% and 6% in most racial/ethnic groups studied, 10%-20% among high-risk populations [8].…”
mentioning
confidence: 99%